Seed Production of Selected Crops in Telangana State, India: Assessment of Demand, Supply and Constraints (Indian Journal of Extension Education, 2022)
The study estimated the gap in demand and supply of seed production in paddy, groundnut and soybean in Telangana state from 2012-13 to 2016-17. There was a surplus in paddyseed production (95 to 216%), which was exported to other states; inconsistency in groundnut seed production and deficit in few years was met through seed imported from Gujarat state; and deficit in soybean (13 to 80%) was met by imports from Madhya Pradesh. The constraints in seed production were assessed through primary data collected during 2017-18, using the multistage random sampling technique. Farmers reported that procurement price of seed (similar to crop prices) was not remunerative. Labour (human and machine) alone accounted for 30-38 per cent of the cost of seed production in soybean and groundnut. Coordination among public and private sector in seed production and distribution is required for addressing the demand and supply gaps.